Can black soldier fly larvae-Desmodium intortum based diets enhance the performance of Cobb500(R) broiler chickens and smallholder farmers' profit in Kenya? - Mutisya, M.M.; Agbodzavu, K.M.; Kinyuru, J.; Tanga, C.M.; Gicheha, M.; Hailu, G.; Salifu, D.; Khan, Z.; Niassy, S. (Elsevier, 2021)
This study aimed to evaluate the performance of broiler chickens fed on 3 black soldier fly larvae (BSFL) (Hermetia illucens) and Greenleaf desmodium (Desmodium intortum)-based meals. We evaluated growth performance, carcass quality, and profitability under various commercial pathways (doorstep, retail, whole, and assorted). Desmodium and BSFL powders were formulated into 3 ratios: T1 25:75, T2 50:50, and T3 75:25. A commercial feed was used as a control. One hundred and twenty mixed-sex 1-day-old broiler chicks (Cobb) were reared in pens for 42 d in a completely randomized design. The chickens were weighed weekly to monitor their growth rate. After the 42-day rearing period, they were slaughtered for carcass quality evaluation and recording of the weights of internal organs. During the initial growth phase (7–21 d), significant effects of fish meal replacement were found on the chickens' average weight (P < 0.001), average daily body weight gain (P < 0.001), average daily feed intake (P < 0.001), and feed conversion ratio (P < 0.001). However, during the second phase (21–42 d), no significant effect of the replacement was detected except on average daily feed intake (P = 0.003). No significant differences were found in terms of the relative weights of internal organs. It was found that Desmodium-BSFL-based feeds were more profitable than the control feed, and the assorted and retail modes of sale generated more revenue compared to when the chickens were sold at doorstep and on whole-chicken basis. The return on investment was higher for a push-pull adopter compared to a non-adopter. The study found that a BSFL-Desmodium mixture can be a valuable replacement for the protein component in conventional feed and would provide a new impetus for the adoption of push-pull.